Pengaruh Gaya Kepemimpinan Visioner, Lingkungan Kerja dan Stress Kerja terhadap Kinerja Pegawai pada Kantor Sekretariat DPRD Kota Pangkajene dan Kepulauan - Riska Amalia; Muhammad Idris (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Employee performance in public sector organizations is closely related to leadership quality, work environment, and the level of work stress experienced by employees. This research examines the relationship between visionary leadership, work environment, and work stress on employee performance at the Secretariat Office of the DPRD of Pangkajene and Kepulauan City. A quantitative approach was applied using survey data collected from 39 employees as research respondents. Data were analyzed using multiple linear regression with the assistance of SPSS to identify both partial and simultaneous effects among the variables studied. The findings indicate that visionary leadership has a positive and significant effect on employee performance, showing the importance of leaders in providing clear direction, motivation, and inspiration in achieving organizational goals. The work environment also demonstrates a positive and significant influence, reflecting that adequate facilities, effective communication, and supportive working conditions contribute to improved employee performance. In contrast, work stress shows a negative effect on employee performance, indicating that excessive workload and role pressure can reduce productivity and effectiveness at work. Simultaneously, visionary leadership, work environment, and work stress significantly influence employee performance. These results emphasize the need for public organizations to strengthen visionary leadership practices, create a conducive work environment, and manage work stress effectively to enhance employee performance and organizational effectiveness.